Cytotoxic and Antibacterial Angucycline- and Prodigiosin- Analogues from the Deep-Sea Derived Streptomyces sp. SCSIO 11594 - Song, Yongxiang (Mar Drugs, 2015)
Two new C-glycoside angucyclines, marangucycline A (1) and marangucycline B (2), along with three known compounds, dehydroxyaquayamycin (3), undecylprodigiosin (4) and metacycloprodigiosin (5), have been identified as products of the deep-sea sediment strain Streptomyces sp. SCSIO 11594. New structures were elucidated on the basis of HRESIMS, 1D and 2D NMR analyses and comparisons to previously reported datasets. Compounds 2 and 4 displayed in vitro cytotoxicity against four cancer cell lines A594, CNE2, HepG2, MCF-7 superior to those obtained with cisplatin, the positive control. Notably, compound 2 bearing a keto-sugar displayed significant cytotoxicity against cancer cell lines with IC(50) values ranging from 0.24 to 0.56 μM; An IC(50) value of 3.67 μM was found when using non-cancerous hepatic cell line HL7702, demonstrating the cancer cell selectivity of 2. Compounds 1–3 were proved to have weak antibacterial activities against Enterococcus faecalis ATCC29212 with an MIC value of 64.0 μg/mL. Moreover, 3 displayed selective antibacterial activity against methicillin-resistant Staphylococcus epidermidis shhs-E1 with an MIC value of 16.0 μg/mL.